Enhancing Chemistry Education through Problem-Based Learning: Analyzing Student Engagement, Motivation, and Critical Thinking - Arsyad, Muhammad; Guna, Saut; Barus, Sebastian (Trigin Institute, 2024)
This research investigates the implementation and outcomes of Problem-Based Learning (PBL) in chemistry education, focusing on its impact on student engagement, motivation, and critical thinking skills. Employing a mixed-methods approach, the study combines quantitative surveys and qualitative interviews to provide a comprehensive analysis of PBL experiences from both student and instructor perspectives. The findings reveal that PBL significantly enhances student performance by fostering a deeper understanding of chemical concepts and improving problem-solving abilities. Additionally, PBL increases student motivation and interest in chemistry through active participation and real-world problem-solving. However, the study also identifies challenges in PBL implementation, including resource constraints, the need for instructor training, and student resistance to the new learning model. Addressing these challenges is crucial for maximizing the benefits of PBL. This research contributes to the growing body of literature on innovative teaching strategies in science education and offers practical insights for educators and policymakers seeking to enhance the effectiveness of chemistry instruction.